METODE PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Muhammad Ibnu Mubarok ,; Rizma Abdul Matin ,; Syahrial Safaat ,; Nurfitria, (JOEL: Journal of Educational and Language Research, 2024)
Learning methods are one of the important components that support or support the successful implementation of the learning process in class. Because of this, it is important to choose the right learning method that will be applied in class so that classroom learning can be carried out successfully and have an impact on students’ success in learning. Indonesian language lessons are one of the subjects that must be taught in elementary schools, this is one of the the reason why Indonesian language lessons must be taught at all levels of education, especially in elementary/MI because it is the basis of all learning. In essence, Indonesian language lessons in elementary schools are about teaching children to be able to communicate using Indonesian, and are aimed at improving students’ ability to communicate in Indonesian effectively and efficiently both orally and in writing. The objectives of this subject will have an impact on learning activities that lead to students being able to communicate using Indonesian. With the existence of Indonesian language learning methods in elementary schools, they can increase knowledge and skills, as a way of preserving culture, developing science and technology, and being able to communicate effectively. Good and correct, and able to express good and polite opinions